Experiences of postnatal contraceptive care during the COVID-19 pandemic: a multimethods cross-sectional study - Judith Rankin; Malcolm Moffat; Claire Sullivan; Robyn Jackowich; Christine Moller-Christensen; Shauna Kelly; Caitlin Thompson (BMJ Open)
Objectives This study aimed to examine the impact of the first COVID-19 lockdown period on access to postnatal contraception (PNC) and wider postnatal care and to explore the experiences of PNC care within the North East and North Cumbria (NENC) Integrated Care System (ICS) during the same period.Design This study reports a subanalysis of the NENC Postnatal Contraception (PoCo) study, an online survey of a convenience sample of women in the NENC ICS who completed pregnancies between 2019 and 2023.Setting Women who completed pregnancies between 2019 and 2023 in the NENC ICS.Participants Out of the total 2509 eligible participants who completed the PoCo survey, women who delivered in April–June 2020, April–June 2021 and April–June 2022 were included within this subanalysis, resulting in 457 eligible survey responses. There were no additional exclusion criteria.Primary and secondary outcome measures Primary outcome measures were PNC uptake and number of healthcare professional contacts during the postnatal period. Secondary outcome measures were self-reported experiences of PNC care.Results Women who delivered in April–June 2020 had fewer postnatal contacts than women who delivered in subsequent non-lockdown cohorts and were less likely to be offered PNC prior to discharge. There were no significant differences in relation to PNC uptake. In qualitative analyses, several women who delivered in 2020 highlighted COVID-19 as a factor perceived to be associated with poor postnatal care. Across all three groups, experiences of PNC care were diverse; feeling pressured to accept PNC was frequently reported.Conclusions While the first COVID-19 lockdown appears to have had a significant impact on women’s experiences of postnatal care, this did not result in a substantive decrease in PNC provision, likely reflecting pre-existing shortcomings. These women and families may benefit from additional support postpandemic to mitigate the potential life course implications of restricted support in the postpartum period, and policy-makers and healthcare providers should continue to explore innovative and patient-centred approaches to improving PNC provision. Future research should continue to evaluate the longer-term impacts of these changes in non-pandemic contexts.